Pengembangan Video Pembelajaran Teknik Vokal sebagai Media Audio Visual Interaktif - Alhafizi, Wahyu Maulana; Hafiz, Alwan (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Learning vocal techniques requires an understanding of physical, technical, and musical aspects, but many students have difficulty mastering diaphragmatic breathing, articulation, resonance, and tone control due to the limitations of media that are only oral or text-based. Therefore, teachers need more flexible and interesting learning media. This research aims to develop vocal technique learning videos as interactive audio-visual media. This research uses the Research and Development (R&D) method with the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 11th grade students of SMA N 1 Masbagik. The results of our research are in the form of vocal technique learning videos as interactive audio-visual media. The results of testing by media experts show that this media is very feasible (85.75%) and material media experts give an assessment that this media is also very feasible (86.2%). Meanwhile, the results of user responses to this media are very high (85.6%). These results indicate that the learning media is effective and very feasible as a medium for learning vocal techniques.